Risk related behavior of the youth, using natural radiation and solariums with diagnosed nevi among residents of villages - Anna Lewandowska; Renata Ożóg; Barbara Laskowska; Tomasz Lewandowski (Journal of Education, Health and Sport, 2017)
Objective: Solar radiation is the most frequent environmental factor influencing the skin, where responsibility for harmful properties are of the ultraviolet radiation. Excessive exposure to ultraviolet radiation significantly increases the risk of occurrence pigmented or non-pigmented skin cancers – melanoma or squamous-cell cancer. Cancerous effect is observed through artificial tanning. International agency for Research on Cancer in 2009 classified the radiation emitted by solar lams as carcinogen factor for skin cancer, equally with other carcinogens, such as arsenic compounds, coal tar and soot